Best practices in mentoring for teacher and leader development - Searby, Linda; Brondyk, Susan K. (Perspectives in mentoring., 2016)
Mentoring in educational contexts has become a rapidly growing field of study, both in the United States and internationally (Fletcher & Mullen, 2012). The prevalence of mentoring has resulted in the mindset that "everyone thinks they know what mentoring is, and there is an intuitive belief that mentoring works" (Eby, Rhodes, & Allen, 2010, p. 7). How do we know that mentoring works? In this age of accountability, the time is ripe for substantiating evidence through empirical research, what mentoring processes, forms, and strategies lead to more effective teachers and administrators within P-12 contexts.This book is the sixth in the Mentoring Perspectives Series, edited by Dr. Frances Kochan former Dean of the College of Education at Auburn University. This latest book in the series, co-edited by Linda J. Searby and Susan K. Brondyk, brings together reports of recent research on mentoring in K-12 settings for new teachers and new principals. The book has already garnered accolades from mentoring experts.